Perancangan Sistem Informasi Pengelolaan Data Posyandu Berbasis Website : (Studi Kasus: Posyandu Matahari) - Albertina Noti Babang; Yustina Rada; Erwianta Gustial Radjah (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Matahari Integrated Service Center (Posyandu) is one of the health service service units located in East Sumba Regency, Wulla Waijelu District, Paranda Village. The activities that are often carried out every month at the posyandu include weighing toddlers, maternal health services, child health, immunizations and health education. The work system at Posyandu Matahari is currently not running well because there are still several shortcomings, including posyandu cadres experiencing difficulties in the data management process, writing registers or data on posyandu target participants repeatedly due to the lack of data storage because the data is currently in the form of paper documents. So ranges are lost, data packets are often damaged and even data packets are damaged. In recording data there are also other obstacles such as the data being written unclearly making it difficult to read, especially when the officer who wrote the data is not there, therefore this research aims to help posyandu cadres in recording data processing and making reports. So the researchers proposed designing a posyandu data management system that includes cadre data, midwife data, toddler data, toddler mother data, pregnant mother data and immunization data. The method used in designing the posyandu data management information system is the waterfall method to design the modeling of a posyandu data management information system. The waterfall method is the earliest software development life cycle (SDLC) approach used for software.